Plantas medicinales usadas en algunas veredas de municipios del altiplano del Oriente antioqueño, Colombia (2011)
ABSTRACT: With the aim of knowing and determining the relative importance of local medicinal plants, an ethnobotanical study was conducted in the farming communities of some townships in six municipalities of the high plains of eastern Antioquia: El Carmen de Viboral, El Retiro, Guarne, La Ceja, Marinilla, and Rionegro, in a region within the lower mountain humid rainforest life zone (bh-MB). Information was compiled on both wild and cultivated medicinal plants that were introduced during the conquest or colonial period and whose use is very ingrained in the communities in this region. With information provided by 17 informants from the different townships, 254 plant species used for medicinal purposes in the high plains of eastern Antioquia were registered from 193 genera belonging to 79 families. Half of the species reported in this study (127) are wild, not actively cultivated, and mainly obtained from areas of secondary vegetation such as roadsides, pastures, scrubby and second growth areas and streamsides, among others habitats. the other 127 species used medicinally in the region were cultivated for nutritional, ornamental, esoteric, rewood, or medicinal purposes, usually in familiar gardens or elds specialized for production of medicinal plants for sale. this study represents a contribution to the knowledge of the medicinal ora of Colombia and the recovery of traditional knowledge on the use of medicinal plants.